2016
DOI: 10.1177/1043659615613418
|View full text |Cite
|
Sign up to set email alerts
|

A Culturally Appropriate Self-Management Program for Hispanic Adults With Type 2 Diabetes and Low Health Literacy Skills

Abstract: The findings may help in further development of tools and strategies for improved T2D self-management in the study population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…Patients indicated that they first needed to accept their situation. After acceptance they realized that they needed to take charge of their own health and care process [22,25,31,46,61,64,66,72,77,80,84,102].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients indicated that they first needed to accept their situation. After acceptance they realized that they needed to take charge of their own health and care process [22,25,31,46,61,64,66,72,77,80,84,102].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, patients with LHL criticized that the content covered in written medical information leaflets or handbooks is often repetitive and rarely novel [115]. This results in patients with LHL describing limited knowledge, experience or expectation prior to the diagnosis that affected them [64]. The majority of participants expressed a need for comprehensive information to be provided, as they had false beliefs of their condition, e.g., equating a cancer diagnosis to a ‘death sentence’ [115].…”
Section: Resultsmentioning
confidence: 99%
“…Especially for diabetic patients who were taking antidepressants, the percentage of low HL was as high as 72% (12). Fortunately, HL among diabetic patients can be improved through instruction (13,14) and improving their communication with others (15) or knowledge of DM (16).…”
Section: ' Introductionmentioning
confidence: 99%
“…The first author conducted the initial analysis and synthesis, and the second author confirmed the results, which are presented in Table 2. Table 1 summarizes characteristics of the seven included studies (Amirehsani et al, 2019;Brunk et al, 2017;Islam et al, 2013;Maglalang et al, 2017;Okoro et al, 2018;Vincent, 2009;Whitney et al, 2017). All studies were published between 2009 and 2019, five since 2017.…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…Four studies' data were collected in participants' original language (such as Spanish or Bengali) by bilingual researcher or moderators. These data were then translated in English for analysis (Amirehsani et al, 2019;Brunk et al, 2017;Islam et al, 2013;Vincent, 2009). Other studies, whose participants were African Americans and Filipino Americans, collected data in English (Maglalang et al, 2017;Okoro et al, 2018;Whitney et al, 2017).…”
Section: Study Characteristicsmentioning
confidence: 99%